Rancang Bangun Sistem Informasi Manufaktur "Sepatu Bordir.ID" Malang Menggunakan Metode Rapid Application Development (Modul: Marketing dan Laporan) - Novi Fadilla Ulfa; Nurudin Santoso; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Sepatu Bordir.ID is a Small and Medium Enterprises (SMEs) in manufacturing sector of shoes production. In 2014, products from Sepatu Bordir.ID begin to be sell in several cities in Indonesia. The shoes sell process is performed by ordering the shoes directly or indirectly. The process of calculating the total payment of the orders is still using calculators, so the accuracy of the process is not really optimal. Besides, the use of social media platforms such us Whatshapp and Instagram to introduce the products makes it less efficient when resellers order shoes. Another problem is found in the entry and reporting process carried out by financial and marketing agents are still using Microsoft Excel, so there is a chance that the data has not been inputted. Based on these problems, a solution is made by developing a website-based technology that is manufacturing information system "Sepatu Bordir.ID" which is implemented in a laravel framework. The phase of requirement engineering of this study produces 24 functional requirements, 1 non-functional requirement and there are three actors that will employ this system, which are the marketing, financial and reseller agents. The results of the requirement engineering were modeled in the design phase using sequence diagrams, class diagrams, component design, database design and interface design and then implemented at the implementation phase. This research used Rapid Application Development method and used HTML, CSS, Javascript and PHP programming languages. The testing phase in this study employed the methods of white box, black box, RAD testing stages, and usability testing. Each of these tests resulted in 100% valid score and usability testing obtained 75 likert which was perceived as an Acceptable.